MENELAAH FAKTOR PENENTU KETERAMPILAN BERBICARA DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Nugroho, Agung; Harbono, Harbono; Ali Yafi, Mohammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Speaking skills are one of the important competencies in Indonesian language learning in elementary schools because they play a role in developing students' thinking, communication, and social interaction skills. However, the speaking skills of lower grade students are still not optimally developed and are influenced by various factors. This study aims to identify the factors that influence students' speaking skills in Indonesian language learning in grade 3 elementary school. The research method used is descriptive qualitative with data collection techniques through observation, interviews, questionnaires, and documentation. The subjects of this study were grade 3 students at an elementary school in Karanganyar Regency, Central Java. Data analysis was conducted using the interactive model of Miles and Huberman (2014). The results showed that students' speaking skills were influenced by various factors, both internal and external. Internal factors included low self-confidence and limited vocabulary, while external factors included students' speaking habits and experiences as well as the learning environment and methods applied by teachers. These findings indicate that the development of elementary school students' speaking skills needs to be carried out in an integrated manner through the strengthening of psychological aspects, language enrichment, and the creation of a participatory and conducive learning environment. Keywords: Speaking Skills; Influencing Factors; Indonesian Language Learning.